Electrocatalytic Activity of Nanohybrids Based on Carbon Nanomaterials and MFe2O4 (M=Co, Mn) towards the Reduction of Hydrogen Peroxide. Issue 8 (25th April 2018) - Gutierrez, Fabiana A.; Mazario, Eva; Menéndez, Nieves; Herrasti, Pilar; Rubianes, María D.; Zagal, José H.; Yañez, C.; Rivas, Gustavo A.; Bollo, Soledad; Recio, F. Javier
Abstract: We report the advantages of hybrid nanomaterials prepared with electrogenerated ferrites (MFe2 O4 ; M: Co, Mn) and multi‐walled carbon nanotubes (MWCNTs) or thermally reduced graphene oxide (TRGO) on the electro‐reduction of hydrogen peroxide. Glassy carbon electrodes (GCE) modified with these hybrid nanomaterials dispersed in Nafion/isopropanol demonstrated a clear synergism on the catalytic reduction of reduction of hydrogen peroxide at pH 13.00. The intimate interaction between MFe2 O4 and carbon nanomaterials allowed a better electronic transfer and a facilitated regeneration of M 2+ at the carbon nanomaterials, reducing the charge transfer resistances for hydrogen peroxide reduction and increasing the sensitivities of the amperometric response. Abstract :